Anaerobic electron acceptor chemotaxis in Shewanella putrefaciens. - Nealson, K H (1995)
Shewanella putrefaciens MR-1 can grow either aerobically or anaerobically at the expense of many different electron acceptors and is often found in abundance at redox interfaces in nature. Such redox interfaces are often characterized by very strong gradients of electron acceptors resulting from rapid microbial metabolism. The coincidence of S. putrefaciens abundance with environmental gradients prompted an examination of the ability of MR-1 to sense and respond to electron acceptor gradients in the laboratory. In these experiments, taxis to the majority of the electron acceptors that S. putrefaciens utilizes for anaerobic growth was seen. All anaerobic electron acceptor taxis was eliminated by the presence of oxygen, nitrate, nitrite, elemental sulfur, or dimethyl sulfoxide, even though taxis to the latter was very weak and nitrate and nitrite respiration was normal in the presence of dimethyl sulfoxide. Studies with respiratory mutants of MR-1 revealed that several electron acceptors that could not be used for anaerobic growth nevertheless elicited normal anaerobic taxis. Mutant M56, which was unable to respire nitrite, showed normal taxis to nitrite, as well as the inhibition of taxis to other electron acceptors by nitrite. These results indicate that electron acceptor taxis in S. putrefaciens does not conform to the paradigm established for Escherichia coli and several other bacteria. Carbon chemo-taxis was also unusual in this organism: of all carbon compounds tested, the only positive response observed was to formate under anaerobic conditions.